1995
DOI: 10.1002/kin.550270503
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced disproportionation of iodomalonic acid

Abstract: The stoichiometry, equilibrium, and kinetics of the photo-induced disproportionation of iodomalonic acid to I-, 12, and tartronic acid have been studied by means of spectrophotometry and iodide selective electrode at 20.0 2 0.2"C, pH 2.0-4.0. At pH > 2.9, only Iand HOCH(COOHI2 are detected as major products and the reaction reaches 100% conversion. At pH < 2.9, 12 and malonic acid are also formed and the reaction stops at a conversion rate less than 100%. Both UV (band with a peak at 360 nm) and visible light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This would lead to a novel oscillatory state or a multiple stability. However, no clear experimental evidence has so far been reported except for the photodecomposition of iodomalonic acid, which is claimed to be acompanied by the autocatalytic formation of I - and I 2 under certain conditions . We started the present study with the expectation that the Briggs−Rauscher (BR) system would provide a clear evidence for the photoautocatalysis that leads to a novel photoinduced bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…This would lead to a novel oscillatory state or a multiple stability. However, no clear experimental evidence has so far been reported except for the photodecomposition of iodomalonic acid, which is claimed to be acompanied by the autocatalytic formation of I - and I 2 under certain conditions . We started the present study with the expectation that the Briggs−Rauscher (BR) system would provide a clear evidence for the photoautocatalysis that leads to a novel photoinduced bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rábai and Hanazaki studied the photochemical decomposition of iodomalonic acid . They showed that iodine, iodide ion, malonic and tartronic acids are among the products of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediates of its photolysis (e.g., ClO) are expected to be involved in composite reactions in the oscillatory system. Photoinduced disproportionation of iodomalonic acid has also been investigated in details and was assumed to be responsible for the peculiar photoresponses of the iodomalonic acid−chlorite ion reaction observed in a semibatch reactor . However, according to Horváth et al, iodomalonic acid plays only a minor role, if any, in the photoresponses, but the iodine−iodide ion−chlorine dioxide subsystem is largely responsible for the response to the illumination in the CDIMA reaction.…”
Section: Introductionmentioning
confidence: 99%